The one - Cass, Kiera (New York, NY : HarperTeen, an imprint of HarperCollinsPublishers, 2015)
"As her Selection approaches its finish, America must decide where her heart truly lies--and Prince Maxon must pick one winner to wear the crown"--Provided by publisher.
Horn Book
Publisher's Weekly
School Library Journal
Horn Book, October 2014
Publisher's Weekly, March 2014
School Library Journal, May 2014
Keywords: Contests -- Juvenile fiction; Marriage -- Juvenile fiction; Princes -- Juvenile fiction; Revolutionaries -- Juvenile fiction; Social classes -- Juvenile fiction; Contests -- Fiction; Love -- Fiction; Marriage -- Fiction; Princes -- Fiction; Revolutionaries -- Fiction; Social classes -- Fiction; Contests -- Fiction; Love stories; Marriage -- Fiction; Princes -- Fiction; Revolutionaries -- Fiction; Social classes -- Fiction; Love stories